Competence of handling medical emergencies among dental graduates and post-graduate students - A cross-sectional questionnaire study - Aveek Mukherji; Mohit Pal Singh; Prashant Nahar; S Bhuvaneshwari; Saurabh Goel; Hemant Mathur (Wolters Kluwer Medknow Publications, 2019)
Introduction: Dentists are encountering a growing number of geriatric and medically compromised patients and at the same time are performing more invasive and possibly painful dental treatments. Medical emergencies are 5.8 times more likely to occur in dental offices than in medical offices. So, it is essential for the dentists to be adequately prepared and equipped to manage the common medical emergencies that may occur during their work. Aims and Objectives: To observe the knowledge, experience, and perceptions of the interns and post-graduate students regarding emergency medical care and its practical application. Materials and Method: A cross-sectional study was carried out among post-graduate students and interns (with or without medical emergency training) of a dental college and hospital through a self-administered structured closed-ended questionnaire. Results: The participants lacked the knowledge to handle medical emergencies and were unconfident to face them. Conclusion: Undergraduate health courses should develop strategies to teach appropriate management of life-threatening emergencies in dental clinics to ensure safer dental healthcare services for the population. The available medical emergency training is alarmingly inadequate.